The Analysis of The Speech Style Used By Steve Harvey's Talk Show in The Episode “Inspiring Young Man Brings Steve Harvey To Tears” - Diana Angela Bria; Heribertus Binawan (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The purpose of this research is to analyze the speech style used by Steve Harvey in the episode